Digital Footprints and Family Harmony: Use of Social Media in Kedai Damar Village, Tebing Tinggi, Serdang Bedagai - Mulia Pohan, Baginda; Sikumbang, Ahmad Tamrin (Jurnal Dakwah dan Komunikasi, 2024)
This research aims to investigate the digital footprint of social media use and its relationship to family harmony in the village. Through a qualitative approach, data was collected through interviews and observations of families in the village. Data was collected by observation and interviews. The informants for this research were 10 families who met the criteria for the purposive sampling technique. The research results stated that families in Kedai Damar Village use social media to make their daily lives easier. The social media they use are WhatsApp, Facebook, Instagram, TikTok and YouTube. Results showed that social media use had a complex impact on family dynamics, with 7 families finding improvements in interpersonal communication and connections, while 3 others faced the challenge of finding the right proportion of social media use to avoid conflict. The implications of the research emphasize the importance of understanding the role of social media in shaping family life in rural areas, as well as designing strategies that support healthy use and have a positive impact on family harmony.